The Influence of Teachers' Certification and Work Motivation on the Professionalism of State Elementary School Teachers - Wilis Winarti; Tri Widayatsih; Suherman Suherman (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of teachers' certification and work motivation on the professionalism of State Elementary School teachers in Suak Tapeh District, both partially and simultaneously. Using a quantitative ex post facto approach, data were collected via questionnaires and documentation from 69 teachers and analyzed using SPSS. The results indicate that both certification and work motivation have significant positive effects individually, with motivation showing a slightly stronger influence. Furthermore, their combined impact is substantially greater, explaining a significant portion of the variance in professional standards. The novelty of this research lies in its localized examination of these interconnected factors within a specific Indonesian district, providing contextual empirical evidence. A key practical implication is that educational policy must not only maintain certification programs but also actively foster teacher motivation through systemic support to maximize professional outcomes. This study contributes to the academic literature by quantifying the synergistic relationship between certification and motivation, and offers actionable insights for local administrators seeking to enhance teaching quality through dual-focused strategies.